The joint properties of dissimilar aluminum plates joined by friction stir welding - Sarsilmaz, Furkan; Caydas, Ulas; Hascalik, Ahmet; Tanriover, Levent (Carl Hanser Verlag, 2010)
Friction stir welding (FSW) can be used to join dissimilar Al alloys which have different mechanical properties without causing any weld zone defects under a wide range of welding conditions. In this study, AA2024 and AA5052 aluminum alloys were successfully joined together using FSW. FSW process parameters such as tool rotational speed and traverse speed were varied to explore their effects on the microstructural and mechanical properties of welded couples. Tension and fatigue tests were carried out and hardness measurements were conducted on cross-sections of the weld zones. Fatigue tests were performed using a fatigue test machine and the fatigue strength was analyzed by drawing S-N curves and critically observing fatigue fracture surfaces of the tested samples. The microstructures of the alloys and fracture surfaces were examined by optical and scanning electron microscopy. Experimental results indicate that microstructural and mechanical properties are significantly affected by changing welding parameters within the chosen range of conditions.
Keywords: Friction stir welding; Dissimilar materials; Fatigue tests